2021
DOI: 10.1002/ptr.7350
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin supplementation in pediatric patients: A systematic review of current clinical evidence

Abstract: This systematic review was designed to determine the clinical efficacy and safety of curcumin supplementation for pediatric patients based on clinical trials in children.We systematically searched electronic databases including PubMed, EMBASE, Web of Science, and Scopus for all studies that investigated curcumin administration in the pediatric population without any time frame limitation. Finally, we identified 16 studies for this review. Clinical efficacy and safety of curcumin were assessed in children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 118 publications
0
21
0
Order By: Relevance
“…Since ancient times, turmeric has been proposed as a natural cure for a variety of diseases. Curcumin, a natural chemical extracted from the rhizome of Curcuma longa (turmeric), has been demonstrated to have antioxidant, antiproliferative, anti-inflammatory, anticancer, cardioprotective, analgesic, antidiabetic, and hepatoprotective properties [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Numerous in vitro, in vivo, and clinical studies have reported that curcumin may have a beneficial effect on liver cirrhosis [ 2 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, turmeric has been proposed as a natural cure for a variety of diseases. Curcumin, a natural chemical extracted from the rhizome of Curcuma longa (turmeric), has been demonstrated to have antioxidant, antiproliferative, anti-inflammatory, anticancer, cardioprotective, analgesic, antidiabetic, and hepatoprotective properties [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Numerous in vitro, in vivo, and clinical studies have reported that curcumin may have a beneficial effect on liver cirrhosis [ 2 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to curcuminoids, which are the most important active ingredient in turmeric, sesquiterpenes, diterpenes, and triterpenoids are other such active components that are also present (Abdel‐Lateef et al, 2016). Numerous studies have revealed the safety and efficacy of curcumin in various diseases and pathological conditions (Bavarsad, Barreto, Hadjzadeh, & Sahebkar, 2019; Ganjali et al, 2017; Heidari, Daei, Boozari, Jamialahmadi, & Sahebkar, 2022; Kunnumakkara et al, 2017; Panahi et al, 2017; Panahi, Ghanei, Bashiri, Hajihashemi, & Sahebkar, 2014; Parsamanesh, Moossavi, Bahrami, Butler, & Sahebkar, 2018; Salmaninejad et al, 2019). Another important health benefit of curcumin that has been shown in many clinical studies is its anti‐inflammatory effect (Peng et al, 2021).…”
Section: Curcuminmentioning
confidence: 99%
“…Curcumin is a safe phytochemical that elicits a wide range of biological actions in the human body. It shows anti-inflammatory, antioxidant, lipid-modulating, anti-thrombotic, immunomodulatory, hepatoprotective, anti-diabetic, anti-tumor, and neuroprotective actions (Qadir et al 2016;Bavarsad et al 2019;Ghasemi et al 2019;Iranshahi et al 2009;Panahi et al 2017b;Parsamanesh et al 2018;Sahebkar and Henrotin 2016;Alidadi et al 2020;Heidari et al 2022;Vahedian-Azimi et al 2022;Mohammed et al 2021).…”
Section: Introductionmentioning
confidence: 99%